Territorial dynamics of agricultural and oil extractivism at the beginning of the 21st century in the department of Meta, Colombia - Devia Acosta, Claudia Yolima; Piñeros Lizarazo, Robinzon (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article presents a mapping of the territorial dynamics of the extractive economies in a part of the Colombian Orinoquía considered the last agricultural frontier of the country. This mapping is an input for the analysis of the spatialization of extractivism that considers the recent transformations in the areas of peasant agriculture and the growth of agro-industrial crop areas, as well as the new extensions of monocultures and oil production. These elements were mapped and temporally compared, the demographic change was also analyzed and, in particular, the accelerated process of urbanization of the population in relation to the phenomenon studied. Later, there were elaborated coremas that synthesize the spatial and temporal dynamics of the extractivisms in the department. From the analysis, it is evident the multiscale dimension of extractivism and the complementarity between oil and agroindustrial expansion in the Orinoquía, in the department of Meta and other regions of the national scale as a result of the international demand of commodities.